KUALITAS PELAYANAN PUBLIK BAGI KAUM DIFABEL - Mayarni Mayarni; Nur Laila Meilani; Zulkarnaini Zulkarnaini (Jurnal Kebijakan Publik, 2018)
The Quality of Public Services for Persons Disabilities. Figures persons with disabilitiesin the province of Riau and Pekanbaru always increase every year (BPS , 2012; Dinas Sosial Riau,2015) . This study aimed to analyze the quality of public services for persons with disabilities inPekanbaru. This research is a qualitative descriptive study. Data were collected by interview andobservation, then analyzed using the technique of interactive analysis. The results showed thatpublic service delivery in the city of Pekanbaru is still not qualified on aspects of accessibility ,competence , and security. Aspects of responsiveness and courtesy has worked well, especiallyin the service organized by formal institutions such as banking, healthcare, and education . Thelack of commitment and cross-sectoral coordination cause accessibility and security aspects inorder to accomodate the unmet needs of persons with disabilities in the city of Pekanbaru.